2.2k views
4 votes
Y = 3 - x 3y + x= 5 ​

User Allenhwkim
by
5.1k points

1 Answer

2 votes

x

3

y

=

5

,

x

+

5

y

=

3

Add

3

y

to both sides of the equation.

x

=

5

+

3

y

x

+

5

y

=

3

Replace all occurrences of

x

with the solution found by solving the last equation for

x

. In this case, the value substituted is

5

+

3

y

.

x

=

5

+

3

y

(

5

+

3

y

)

+

5

y

=

3

Solve for

y

in the second equation.

Tap for more steps...

x

=

5

+

3

y

y

=

1

Replace all occurrences of

y

with the solution found by solving the last equation for

y

. In this case, the value substituted is

1

.

x

=

5

+

3

(

1

)

y

=

1

Simplify

5

+

3

(

1

)

.

Tap for more steps...

x

=

2

y

=

1

The solution to the system of equations can be represented as a point.

(

2

,

1

)

The result can be shown in multiple forms.

Point Form:

(

2

,

1

)

Equation Form:

x

=

2

,

y

=

1

User Mattorb
by
5.0k points